2020
DOI: 10.1074/jbc.ra120.012732
|View full text |Cite
|
Sign up to set email alerts
|

In vivo two-photon microscopy reveals the contribution of Sox9+ cell to kidney regeneration in a mouse model with extracellular vesicle treatment

Abstract: Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) have been shown to stimulate regeneration in the treatment of kidney injury. Renal regeneration is also thought to be stimulated by the activation of Sox9+ cells. However, whether and how the activation mechanisms underlying EV treatment and Sox9+ cell-dependent regeneration intersect is unclear. We reasoned that a high-resolution imaging platform in living animals could help to untangle this system. To test this idea, we first applied EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Researches have shown that MSCs locate to injured areas via direct interaction and the paracrine effect [12,13], while being less dependent on the differentiation function [14]. Through marking, it is found that, after being injected into the body, MSCs can be specifically located in the injured zones of the kidney [15][16][17]. The molecular mechanisms of MSC homing are based on a multistep model, including initial tethering by selectins, activation by cytokines, arrest by integrins, diapedesis or transmigration, and migration toward chemokines [18].…”
Section: Biological Characteristics Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches have shown that MSCs locate to injured areas via direct interaction and the paracrine effect [12,13], while being less dependent on the differentiation function [14]. Through marking, it is found that, after being injected into the body, MSCs can be specifically located in the injured zones of the kidney [15][16][17]. The molecular mechanisms of MSC homing are based on a multistep model, including initial tethering by selectins, activation by cytokines, arrest by integrins, diapedesis or transmigration, and migration toward chemokines [18].…”
Section: Biological Characteristics Of Mscsmentioning
confidence: 99%
“…Chen et al proposed that the glial-derived neurotrophic factor-modified ADMSC-Exos stimulate the perivascular capillaries in tubulointerstitial fibrosis by activating the SIRT1/eNOS pathway [ 76 ]. In addition, previous research also suggested that ADMSC-Exos upregulate the expression of the transcription factor Sox9 of TECs, and the offspring of Sox9 + cells facilitate regeneration of renal tubules rather than fibrotic transformation, thus slowing the AKI-CKD transition [ 17 , 77 ].…”
Section: Msc-evs and Kidney Diseasesmentioning
confidence: 99%
“…There are stem/progenitor cells in tubules, especially proximal tubules [ 5 , 11 , 21 , 24 , 64 , 68 ]. Most of them are capable to differentiate into tubular epithelial cells and even could differentiate into mesodermal lineages such as adipogenic, osteogenic, and chondrogenic lineages.…”
Section: The Origin Of Stem/progenitor Cells In the Adult Kidneymentioning
confidence: 99%
“…It has been found that Sox9 + cells are in adult kidney, which own the high capacity of proliferation and mesodermal lineage differentiation [ 70 ]. These stem/progenitor cells are primarily located in proximal tubules, and they have epithelial polarity and brush border [ 68 ]. These cells express CD133 and Lgr4, the markers of progenitor cells, but have a negative expression of Pax-2 or common MSC markers.…”
Section: The Origin Of Stem/progenitor Cells In the Adult Kidneymentioning
confidence: 99%
See 1 more Smart Citation